(untitled) (Research, Society and Development, 2023)
Malaria caused by Plasmodium vivax can evolve into a wide spectrum of clinical disorders such as anemia, thrombocytopenia and other diseases and cause irreversible damage in children, so the main objective of this study is to show the impact of malaria on children in Brazil caused by Plasmodium vivax. And its specific objectives are: To carry out a brief presentation on the epidemiological aspects of malaria. Highlight P. vivax malaria; show the impact of malaria on children in Brazil caused by P. vivax. Methodology, this is a bibliographical research with a narrative review and a qualitative approach. As a result, it was observed that malaria caused by P. vivax affects all age groups, however, it is a greater threat to children, therefore, its consequences were very serious on the children’s neurological systems. Malaria caused by P. vivax resulted in low cognitive performance in the age group of 4 to 7 years, it is assumed that the impact of malaria on cognitive function is not prolonged. However, the majority had moderate exposure, with episodes up to 2 years of age or older.